1998
DOI: 10.1002/(sici)1096-9071(199806)55:2<147::aid-jmv11>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A survey for 32 nucleotide deletion in the CCR‐5 chemokine receptor gene (Δccr‐5) conferring resistance to human immunodeficiency virus type 1 in different ethnic groups and in chimpanzees

Abstract: The 32 nucleotide deletion in the CCR-5 chemokine receptor gene referred to as deltaccr-5 has been shown to confer resistance to HIV-1. Using PCR, 1,105 human subjects and 33 common chimpanzees were genotyped attributing them to one of the three possible genotypes: wild-type homozygote (w/w); deltaccr-5 homozygote (deltaccr-5/deltaccr-5) and deltaccr-5/wild-type heterozygotes (deltaccr-5/w). The ethnic groups investigated included different Middle Eastern nationalities (mainly Arab) and Russians. Carriers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[17][18][19] The delta32 allele is more prevalent in European and European-derived populations (about 10-20 percent) but almost absent or extremely rare among African and East Asian ethnic origins. Based on a previously published study, this allele has a prevalence of about 2.5 percent in the Iranian healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The delta32 allele is more prevalent in European and European-derived populations (about 10-20 percent) but almost absent or extremely rare among African and East Asian ethnic origins. Based on a previously published study, this allele has a prevalence of about 2.5 percent in the Iranian healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1-infected chimpanzees do not generally progress to AIDS (Heeney et al, 1993), although a few chimpanzees exposed to multiple isolates of HIV have been reported to have declining CD4 counts and progressive disease (Novembre et al, 1997;Davis et al, 1998). Mutations that have been associated with resistance to infection or delayed disease progression in humans such as the D32 mutation in CCR5 coreceptor have not been identified in chimpanzees (ten Haaft et al, 2001;Voevodin et al, 1998), although they have recently been shown to exhibit multiple copies of the CCL3L1 (macrophage inflammatory protein-1a-P) gene (Gonzalez et al, 2005). Various hypotheses have been developed to account for control of HIV infection in chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…it was demonstrated that 15.0-20.0% of caucasian individuals were heterozygous for the CCR5-∆32 allele and 1.0% or less was homozygous for this variant allele (59). further studies demonstrated that the CCR5-∆32 allele was present in ~10.0% of the European descendants, was rarely observed in asia and was virtually absent in the native population from sub-Saharan africa (57,(60)(61)(62). A study of the allelic frequency of CCR5-∆32 in 18 european populations revealed an interesting north-south gradient, with the highest frequencies of the variant allele being observed in the finnish and modrvinian populations (16.0%) and the lowest in Sardinia (4.0%) (63).…”
Section: Tnf-a Tnf-β and The Tnf Receptor Genesmentioning
confidence: 99%